Análise da flutuação das populações de aedes aegypti e aedes albopictus em uma escola de Cuiabá-MT - Oliveira, Thomas Eduardo Schiffino de; Musis, Carlo Ralph de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The expressive increase of the population of Cuiabá unleashed a disorderly growth of the city, accompanied by a deficient infrastructure and basic sanitation, thus establishing favorable conditions for the proliferation of vectors of dengue (Aedes aegypti) and yellow fever (Aedes albopictus) in the region, and these endowed great power of adaptation to environments inhabited by humans. Keeping this in view, the aim of this work was to analyze the influence of microclimatic factors in the fluctuations of the populations of Aedes aegypti and Aedes albopictus in a school of the periphery of Cuiabá between January and August 2012, making use of the differentiated model of oviposition trap (ovitrap). The collection of the biotic data (number of eggs) was made in school André Avelino Ribeiro at intervals of fifteen days and the abiotic data: air temperature, relative humidity and rainfall been obtained by means of weather station of the National Institute for Space Research. The results indicated that precipitation was the only microclimatic factor at influencing the proliferation of the dengue vector in school. Significant differences were found for the number of eggs collected in the rainy season in relation to the dry season. However, it was observed expressive values for the number of eggs in this season, indicating that even in the dry period the incidence of the species may be high. Furthermore, the high indices of egg density and vector, as well as of positivity of the ovitrap observed in school have revealed that the place configures itself as a pole of proliferation and dissemination of specie Aedes aegypti.